ANALISIS NUMERIK PROFIL SEDIMENTASI PASIR PADA PERTEMUAN DUA SUNGAI BERBANTUAN SOFTWARE FLUENT - Fatahillah, Arif (Kadikma, 2014)
Abstract.Sand is one material that is very useful for human life that is often used to build a house that will be used as a human habitation. But not all areas of the river containing sand stored below the surface of the water, it depends on various factors such as the speed of the river flow, pressure, and position of the area of the river (curves, straight or it could be a meeting between the two rivers). In this study constructed a model of the shape of sand sedimentation analysis of the problems and solve the problem by using the volume up (finite volume method). The model is constructed based on the pressure and flow rate of the river, which is expected to know about the profile picture of sand sedimentation on a wide range of pressure and flow velocity pattern of the river. Based on the results of the simulation it was concluded that if both channels of the river has a flow rate of pressure and speed the same then the area of sand sedimentation areas potentially occur before the second meeting of the river, whereas if it has a level of pressure and velocity will be different after the confluence area with ideal conditions ie pressure and velocity of the river branch is higher than the main river. Keywords :Sedimentation, Finite Volume Method